Visual hallucinations in neurosurgery: A systematic review and two case insights into Charles Bonnet Syndrome - Erica Grasso; Giulio Bonomo; Francesco Certo; Giacomo Cammarata; Giuseppe M.V. Barbagallo (Brain and Spine)
Introduction: Visual disturbances in brain tumor patients occur as a direct consequence of tumor location or as a complication after surgery. These can range from minor vision changes to severe impairments, including visual hallucinations. Research question: Charles Bonnet Syndrome (CBS) is an underrecognized cause of complex visual hallucinations in patients with visual system disorders, particularly following neurosurgical interventions. We present two cases of CBS following neurosurgical procedures, recruited from our department. Materials and methods: Detailed patient histories, neurological and ophthalmologic evaluations, magnetic resonance imaging (MRI), computerized perimetry, electroencephalogram (EEG), and psychiatric assessments were conducted. A systematic literature review was also performed, focusing on CBS in the context of neurosurgery. Results: The literature review included 13 studies with 17 patients diagnosed with CBS related to neurosurgery. The average age was 54.8 ± 16.5 years. CBS was associated with various pathologies, including mesial temporal lobe sclerosis, glial tumors, and pituitary adenomas. Most CBS cases (76 %) developed post-surgery. CBS onset was linked to extra-axial tumors causing direct mechanical compression of the optic chiasma or nerve, which often resolved completely after tumor excision. Intra-axial tumors were more likely to cause CBS post-operatively, likely due to surgical trauma affecting the optic tracts or visual cortex, and often required additional treatment. Discussion and conclusion: CBS is frequently underrecognized in neurosurgical patients. Differentiating between extra-axial and intra-axial tumor involvement is critical for appropriate treatment. Standardized diagnostic and treatment protocols are needed to improve outcomes, and further research is essential to better understand CBS mechanisms in neurosurgical contexts.